2007
DOI: 10.1590/s0037-86822007000500008
|View full text |Cite
|
Sign up to set email alerts
|

Associação de metemoglobinemia e deficiência de glicose-6-fosfato desidrogenase em pacientes com malária tratados com primaquina

Abstract: RESUMO Este estudo teve como objetivo verificar a ocorrência de metemoglobinemia em indivíduos deficientes da glicose-6-fosfato desidrogenase

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 20 publications
(5 reference statements)
0
7
0
5
Order By: Relevance
“…In G6PDd patients, a significantly higher occurrence of MetHb was observed following oral therapy with PQ when compared to non-G6PDd individuals (Santana et al 2007, Ferreira et al 2011). In Nicaragua, however, administration of 10-20 mg of PQ base daily over 14 days to 321 Miskito Indians with chronic malaria did not lead to any case of secondary adverse events (Thaeler Jr et al 1953).…”
Section: Resultsmentioning
confidence: 88%
“…In G6PDd patients, a significantly higher occurrence of MetHb was observed following oral therapy with PQ when compared to non-G6PDd individuals (Santana et al 2007, Ferreira et al 2011). In Nicaragua, however, administration of 10-20 mg of PQ base daily over 14 days to 321 Miskito Indians with chronic malaria did not lead to any case of secondary adverse events (Thaeler Jr et al 1953).…”
Section: Resultsmentioning
confidence: 88%
“…A significant increase in methaemoglobinaemia was observed following oral therapy with PQ in patients with P. vivax presenting G6PDd [115,116]. Additionally, in Colombia, an association between haemolysis and physical exercise was observed in individuals with reduced G6PD activity [117].…”
Section: Resultsmentioning
confidence: 99%
“…However the evidence is not yet clear in this regard. Santana et al [50] showed that in a group of patients developing methaemoglobinaemia following primaquine therapy, 51% were G6PD deficient (G6PD deficiency in those without methaemoglobinaemia was 8.7%). However, Ferreira et al failed to demonstrate a similar association [51].…”
Section: Methodsmentioning
confidence: 99%